Carotid arterial mechanics as useful biomarker of extracellular matrix turnover and preserved ejection fraction heart failure. (25th May 2020) - Zhou, Kevin Ning; Sung, Kuo‐Tzu; Yen, Chih‐Hsuan; Su, Cheng‐Huang; Lee, Ping‐Ying; Hung, Ta‐Chuan; Huang, Wen‐Hung; Chien, Shih‐Chieh; Tsai, Jui‐Peng; Yun, Chun‐Ho; Chang, Shun‐Chuan; Yeh, Hung‐I; et al.
Abstract: Aims: We aimed to investigate the functional alterations, diagnostic utilization, and prognostic implication of carotid arterial deformations in subjects with cardiovascular risk factors and heart failure (HF) with preserved ejection fraction (HFpEF). Methods and results: Among 251 prospectively participants (mean age 66.0 ± 9.8 years, 65.7% female) in a single centre between December 2011 and September 2014, carotid artery deformations including circumferential strain (CCS)/strain rate and radial strain were analysed by two‐dimensional speckle tracking. We further related these carotid artery deformation indices to HF biomarkers and cardiac structure and function by echocardiography and explored their prognostic values. Significant reductions of CCS, circumferential strain rate, and circumferential radial strain were observed across control ( n = 52), high risk ( n = 147), and HFpEF ( n = 52) (trend P ≤ 0.001). Aging, hypertension, HFpEF, and higher pulse rate showed independent associations with reduced CCS by stepwise multivariate regressions (all P < 0.05). Higher CCS was inversely associated with better cardiac remodelling and functional indices, and lower multiple HF biomarkers (all P ≤ 0.005). After adjustment, higher CCS was independently associated with better global ventricular longitudinal strain/early diastolic strain rate, lower matrix metalloproteinase‐2, and N‐terminal propeptide of procollagen type III levels (adjusted coef: −0.08 and −19.9, all P < 0.05). During a median follow‐up of 1406 days (interquartile range: 1342‑1720 days), CCS less than 3.28% as a cut‐off had markedly higher HF events [Harrell's C: 0.72, adjusted HR: 2.20 (95% confidence interval: 1.24, 3.16), P = 0.008]. CCS also showed significantly improved risk prediction for HF over global ventricular longitudinal strain (net reclassification index: 48%, P = 0.001; integrated discrimination improvement: 1.8%, P < 0.001). Conclusions: Carotid artery deformations using two‐dimensional speckle‐tracking imaging showed novel mechanistic insights on functional arterial alterations reflecting coupled arterial‐ventricular pathophysiology. Utilization of such measure may further provide additive prognostic value to advanced myocardial functional assessment.